Super high resolution numerical weather prediction model simulation of tiny anticyclones observed at the Hong Kong International Airport - Chan, PW; HON, KK; LI, QS (MAUSAM, 2023)
As a follow-up study of the observation of tiny anticyclones by short range LIDAR at the Hong Kong International Airport, super high model numerical weather prediction model simulation of the airflow is performed at a spatial resolution of 50 m. The simulation successfully captures the tiny anticyclonic flow, suggesting that such flow could partly arise from terrain effect on the airflow at the airport. The variability of the winds as observed by an anemometer and as forecast by the model compare well, suggesting that the simulations are realistic. Two case studies are considered. The results could be useful for reference by weather forecasters at the other airports in monitoring and studying terrain-disrupted airflow.